Difficulties and Dilemmas of Supervisors in Ukraine - Kryvokon, Nataliia I. (Psychological Counseling and Psychotherapy, 2021)
The publication is devoted to identifying and detailing the problems that arise in the implementation of supervision in Ukraine. The relevance of the research topic is due to the increased demand for supervision in connection with the desire to conceptualize, institutionalize and regulate the organization of this type of activity as a component of psychological support for domestic psychologists and other specialists in the humanitarian profession, the promotion and development of a system of psychological support and support of these specialists, and is also associated with the growth demand for psychological and social assistance to clients during the COVID-19 pandemic. Based on theoretical analysis, personal experience, and the results of work with a focus group (supervisors working with psychologists and social workers - case managers, 10 people in total), the author's position on the professionally important competencies of supervisors is given, and characteristics of the main difficulties with which supervisors encounter when carrying out their activities, in particular, and in a remote mode of work. A classification of problematic issues and dilemmas that are inherent in supervisory practice in Ukraine at this stage is proposed. The following groups of problems were identified: 1) associated with the peculiarities of establishing professional interaction in supervision; 2) ethical dilemmas and personal difficulties; 3) organizational and administrative. Within the first group, there are considered the difficulties of expressing the authentic and mature position of the supervisor; trust forming in the relationship; views on the nature of power / subordination relations; compliance with professional limits; confidentiality; ensuring the multifunctionality of supervision, etc. The second group includes difficulties related to the mismatch of ideas about the purpose and results of supervision of the customer, the supervisant and the supervisor; with the peculiarities of the formation and course of role and / or internal conflicts; maintaining a balance between creativity and administration; general ethical dilemmas of representatives of anthropological professions, etc. Among the problems of the third group are the difficulties in confirming the status, relevant competence and qualifications of the supervisor, as well as the need to respond to the challenges of the COVID-19 pandemic regarding the organization of online supervision.